Pengaruh Konten Sepakbola Liga Inggris di Aplikasi Vidio terhadap Minat Menonton Grup Manchester United Fans Indonesia di Telegram - Kelvin Roberto Maksindo Manurung; Oky Oxcygentri; Ema (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Football has a global appeal, including in Indonesia, as reflected by the high level of public interest in the sport. The advancement of technology allows fans to watch matches through services such as Vidio. This study focuses on the use of football services and fan communities, specifically the